Triterpenoid saponins from root bark of Zanha golungensis (Sapindaceae). (30th January 2015) - Lavaud, Catherine; Sayagh, Charlotte; Humbert, Franck; Pouny, Isabelle; Delaude, Clément
Graphical abstract: Highlights: Five new saponins with zanhic acid as aglycone were characterized. First depth phytochemical report on chemical compounds from Zanha golungensis . Esterified glycosides with rarely 3, 3-dimethylacryloyl and niloyl residues. The β-d -(4- O -acylated)-fucopyranosyl residue characteristic of Sapindaceae. Abstract: The chemical investigation of the methanolic extract from root bark of Zanha golungensis Hiern led to the isolation of five new and one known triterpenoid saponins. Their structures were elucidated by full analysis of their spectroscopic data and by partial hydrolysis. These glycosides contain zanhic acid as aglycone, a rare oleanane-type triterpenoid found in species belonging to Sapindaceae, Caryophyllaceae, Asteraceae, and Fabaceae. Two new saponins are esterified saponins by 3, 3-dimethylacryloyl and 3-hydroxy-2-methyl-butanoyl residues located on the sugar part. The new compounds were named zanhasaponins D–H following previous isolation of similar compounds from Zanha africana .